Profile of Science Literacy Ability and Science Learning Outcomes of Riyadul Mubarok Integrated High School Students - Maya Ainul Quroh; Siti Patonah; Ari Susatyo Nugroho; M. Syaipul Hayat (Green Publisher Indonesia, 2025)
Indonesia's scientific literacy is in 70th position out of 78 countries based on PISA 2018. This research aims to determine (1) the scientific literacy abilities of Riyadul Mubarok Integrated High School students in class X on renewable energy material using PISA test questions; and (2) Learning outcomes of Riyadul Mubarok Integrated High School students on renewable energy material. The selected sample was 20 class X students using purposive sampling technique. This type of research is descriptive qualitative using daily values ​​on renewable energy material for learning outcomes and PISA test questions totaling 6 essay questions. This research shows that the learning outcomes of Riyadul Mubarok Integrated High School students are in the medium category with an average score of 77.95, which is slightly above the KKM. Meanwhile, the results of scientific literacy on the three indicators show (1) the average value of scientific literacy ability on the indicator of identifying scientific problems is 40, which means that students' scientific literacy ability is in the low category. (2) the results of scientific literacy skills in the indicator explaining scientific phenomena are in the medium category with an average score of 62. (3) the results of scientific literacy skills in the category of using scientific evidence are in the low category with an average score of 37. Literacy scores Overall student science is 55 which is included in the medium category, this is in accordance with the results of the scientific literacy test conducted by PISA in 2018